Selective Use of Interoperability on Mobile Payment Services in Brazil - Quelho, Renata Tonicelli de Mello (Law, State and Telecommunications Review, 2015)
Purpose ”“ The article identifies the underpinnings of the concept of interoperability in the telecommunications and payment systems in Brazil. Methodology/approach/design ”“ The article uses a comparative methodology on the standard of interoperability. Findings ”“ It identifies the context and peculiarities of the interoperability in telecommunications and mobile payment systems in Brazil. Practical implications ”“ The article helps identifying the basic components of telecommunications and payment systems in the context of the new mobile payment systems. Originality/value ”“ It analyzes Brazil's practice on the topic of interoperability and payment systems.